Pengaruh Interaksi Peer Group dan Self-esteem Terhadap Preferensi Pemakaian Krim Pemutih Kulit Pada Remaja Perempuan - Hanna Oliviati, Nur; Ratri Rahmiaji, Lintang (Interaksi Online, 2021)
Peer group interaction and self-esteem play an important role in the lives of adolescents because adolescence is a time of transition and identity exploration. Teenagers frequently want to be recognized by their peers during this time period. Furthermore, adolescents are said to be preoccupied with their appearance. One of the things that teenage girls can do to achieve this recognition is to use a skin whitening cream. The goal of this study was to see how peer group interactions affected preferences for skin whitening cream usage, as well as how self-esteem affected preferences for skin whitening cream usage in adolescent girls. Non-probability sampling was used, with a total sample of 100 respondents being adolescent girls aged 15 to 21 years in Semarang City who used skin care products. Based on hypothesis testing using simple regression analysis, it is revealed that: first, the significance value of the peer interaction variable (X1) is 0.000 (0.05), indicating that peer group interaction and self-esteem have a significant influence on usage preferences. skin whitening cream in adolescent girls, where the direction is positive, implying that the higher the adolescent's preference for using skin whitening cream, the higher the adolescent's preference for using skin whitening cream. Then the self-esteem variable has a value of 0.000 (0.05). That is, the self-esteem variable (X2) has a significant negative effect on the preference for skin whitening cream (Y), indicating that the higher the self-esteem, the lower the adolescent's preference for using skin whitening cream. Suggestions for future research include the ability to conduct research with other independent variables that may affect the preference for using skin whitening creams besides peer group and self-esteem in order to gain more knowledge about preferences for using skin whitening creams.